First principles study on sodium de-intercalation from NaMnPO4. (2022) - Dima, R.S.; Maleka, P.M.; Maluta, E.N.; Maphanga, R.R.
Abstract: The importance of energy generation and storage cannot be overstated, given rising energy demands and the depletion of fossil fuels. Because of their low cost, abundance of elements, strong reversibility, and moderate energy density, sodium-ion batteries have piqued interest as a possible alternative for large-scale electrochemical energy storage. Significant advances in cathode, anode, and electrolyte materials are still required for sodium-ion batteries to attain equivalent performance to existing lithium-ion batteries. To provide critical fundamental insights into electrode materials and to ease the development of materials for sodium-ion batteries, computational techniques have been widely used in connection with experimental investigations. In this work, we have effectively investigated the electrochemical performance of the maricite sodium Manganese phosphates (NaMnPO4 ) as a cathode material for the sodium-ion batteries using systematic first-principles calculations based on density functional theory. On comparing PBE, PBEsol, and GGA + U functionals, the findings showed that the GGA + U approximation reproduced structural parameters and energy band gap values well and was used to further analyse the electrochemical performance of the de-intercalated systems of NaMnPO4 . There band gap values for PBE, PBEsol, and GGA + U are 1.297 eV, 1.510 eV and 3.321 eV, respectively. The voltage window for NaMnPO4 is found to be ranging between 5.132 V and 4.655 V. Also, the results reveal that the metallicity of maricite NaMnPO4 grows progressively during the Na extraction process and the system becomes a semiconductor on the last extraction.